Integral of (3-ln*x)/x dx
The solution
Detail solution
-
There are multiple ways to do this integral.
Method #1
-
Let u=3−log(x).
Then let du=−xdx and substitute −du:
∫(−u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫udu=−∫udu
-
The integral of un is n+1un+1 when n=−1:
∫udu=2u2
So, the result is: −2u2
Now substitute u back in:
−2(3−log(x))2
Method #2
-
Rewrite the integrand:
x3−log(x)=−xlog(x)−3
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−xlog(x)−3)dx=−∫xlog(x)−3dx
-
Let u=x1.
Then let du=−x2dx and substitute −du:
∫(−ulog(u1)−3)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫ulog(u1)−3du=−∫ulog(u1)−3du
-
Let u=log(u1)−3.
Then let du=−udu and substitute −du:
∫(−u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫udu=−∫udu
-
The integral of un is n+1un+1 when n=−1:
∫udu=2u2
So, the result is: −2u2
Now substitute u back in:
−2(log(u1)−3)2
So, the result is: 2(log(u1)−3)2
Now substitute u back in:
2(log(x)−3)2
So, the result is: −2(log(x)−3)2
Method #3
-
Rewrite the integrand:
x3−log(x)=−xlog(x)+x3
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−xlog(x))dx=−∫xlog(x)dx
-
Let u=x1.
Then let du=−x2dx and substitute −du:
∫(−ulog(u1))du
-
The integral of a constant times a function is the constant times the integral of the function:
∫ulog(u1)du=−∫ulog(u1)du
-
Let u=log(u1).
Then let du=−udu and substitute −du:
∫(−u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫udu=−∫udu
-
The integral of un is n+1un+1 when n=−1:
∫udu=2u2
So, the result is: −2u2
Now substitute u back in:
−2log(u1)2
So, the result is: 2log(u1)2
Now substitute u back in:
2log(x)2
So, the result is: −2log(x)2
-
The integral of a constant times a function is the constant times the integral of the function:
∫x3dx=3∫x1dx
-
The integral of x1 is log(x).
So, the result is: 3log(x)
The result is: −2log(x)2+3log(x)
-
Now simplify:
−2(log(x)−3)2
-
Add the constant of integration:
−2(log(x)−3)2+constant
The answer is:
−2(log(x)−3)2+constant
The answer (Indefinite)
[src]
/
| 2
| 3 - log(x) (3 - log(x))
| ---------- dx = C - -------------
| x 2
|
/
∫x3−log(x)dx=C−2(3−log(x))2
The graph
Use the examples entering the upper and lower limits of integration.